Leadership in Action Inklings - Whatever Happened to The Skyhook? - Campbell, David P. (Center for Creative Leadership, 1998)
David Campbell, In looking through his files, recently came across a 1966 article in Science. It got him thinking.
Title from content provider
Keywords: Leadership